Formulasi Dan Evaluasi Mutu Fisik Sediaan Body Scrub Cream Varietas Ubi Jalar Orange Dan Ubi Jalar Putih Dalam Fase Air Dan Minyak - Syaekhoni Laelatul Latifah; Pudjono Pudjono; Resa Frafela Rosmi (Jurnal Farmasi Universitas Peradaban, 2022)
Free radicals are one of the causes of premature aging due to oxidative stress in the body, such as rough, dull, and dry skin. This triggers the need for skin protection against free radicals. One of the natural ingredients that can be used is sweet potato (Ipomoea batatas L.). The purpose of this study was to determine the antioxidant activity of body scrub cream preparations of orange sweet potato and white sweet potato varieties and to determine variations in body scrub cream formulations that were effective as antioxidants. Detection of beta-carotene content by TLC using petroleum ether/benzene (9:1) eluent showed results that were in accordance with the comparison standard of beta-carotene in both orange and white sweet potatoes showing yellow spots with an Rf value of 0.8. The body scrub cream in this study was made with formulas F1, F2, and F3 for orange sweet potatoes and formulas F4, F5, and F6 for white sweet potatoes. The results showed that the F3 formula had greater spreadability, while the F3 and F6 formulas provided a longer adhesion time, and did not irritate the skin. The antioxidant activity test using the DPPH (1,1-diphenyl-2-Picrylhydrazil) method showed that the body scrub cream with the formula F1, F2, F3, F4, F5, and F6 had antioxidant activity with an IC50 value of 30,38 μL/mL; 19,37 μL/mL; 11,18 μL/mL; 73,91 μL/mL; 40,04 μL/mL; and 33,19 μL/mL. The orange sweet potato variety with a concentration of 50% and an IC50 value of 11,18 μL/mL was the best antioxidant.